Amorphous carbon nanorods as a precursor for carbon nanotubes - Suarez-Martinez, Irene; Marks, Nigel (Pergamon, 2012)
The transformation of amorphous carbon nanorods into multi-wall nanotubes is studied using molecular dynamics. The effect of the density, width and shape of the initial nanorod is investigated. High-temperature annealing simulations show that the transformation is a robust process which occurs at all densities, regardless of the nanorod shape. The least defective nanotubes arise from tetrahedral amorphous carbon precursors with an initial density of 3 g/cc. By excising selected regions of the nanorod, we show that the perimeter in cross-section determines the tube diameter, with the number of walls being primarily controlled by the density of the rod. This transformation suggests an alternative approach for generating carbon nanotube networks in the laboratory using ion-beam deposition in combination with lithography.